IMPLEMENTASI PERFORMANCE MANAGEMENT SYSTEM DENGAN DIMENSI FOUR LEVERS OF CONTROL PADA UNIT APRON MOVEMENT CONTROL (AMC) DI BANDAR UDARA SUPADIO PONTIANAK - WALID JUMLAD; PUTRI ANGGRIYANA (Jurnal Manajemen Dirgantara, 2024)
A performance management system is a tool companies need to manage an organization to support achieving business goals and sustainability. One of the application models is with the Four Levers of Control which has advantages in the performance control control system. This study aims to determine the application of the performance management system by utilizing the four levers of control model in the apron movement control unit of PT. Angkasa Pura II Supadio Pontianak Airport. The research was conducted from August 1, 2023, to September 29, 2023. Using a qualitative descriptive research design, in the form of primary and secondary data obtained from company documents, interview information, and observations made in the Airside Operation section. Results indicate that the movement control apron unit has applied the four levers of control model as seen from the application of the belief system. This is guided by the vision, mission, and fundamental values through various communication processes such as morning briefing, employee recruitment process, internal-external meetings, socialization through banner flyers, and exemplary behavior of superiors to their subordinates. The boundary system shows understanding and realization of the existence of behavioral limits set by the company. Includes detailed policies with penalties for code of conduct violations. The company's diagnostic control system monitors and supervises performance through division unit coordinator reports and evaluations to be used as a tool to minimize errors. The interactive control system is reflected in the existence of a discussion forum provided for subordinates to convey suggestions, ideas, and concerns for future improvements.